(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to know the extent of awareness of the students of the Department of Information Science of the role of citation and reference management programs in scientific research. To achieve this, the researchers designed a questionnaire divided into three axes and used the case study approach. The tool was distributed randomly to the students of the department, and the questionnaire was filled out by 77 students. The results of the study showed that the responding sample members were aware of the concept of citation and reference management programs from a theoretical perspective only, at a rate of (59.7%). The source of the "college or university library" came in second place for sources of introducing students to citation and reference management programs, with a number of responses reaching 12, at a rate of 15.6%. The results also indicated an increase in the percentage of the program (End Note knowledge and fame) among the students of the Department of Information Science who responded to the data collection tool, which reached a rate of (49.4%). The program (End Note) also came in first place with a rate of 73.2%, with a response of 41 students out of the total number of students, for the programs they wish to train on. The study came out with recommendations including: increasing awareness of the importance of citation management programs among all students of the Information Science Department, providing training courses and workshops on citation and reference management programs and their role in documenting scientific research and linking the importance of documentation to avoiding scientific plagiarism and achieving academic integrity, designing a guide that explains the mechanism for using and activating citation and reference management programs, and finally integrating the topic of citation and reference management programs into the academic curricula, especially the scientific research skills course, to provide students with the skills to use technology.